IgA Nephropathy: Research Status and Therapeutic Progress with Integrated Traditional Chinese and Western Medicine - Xianyi Huang; Yun Tian (Journal of Artificial Intelligence and Information, 2026)
Immunoglobulin A nephropathy (IgAN) is the most common primary glomerulonephritis worldwide and a leading cause of end-stage renal disease (ESRD). Epidemiological data indicate that China has approximately 4.59 million IgAN patients, with only 570,000 diagnosed, imposing a substantial economic burden. In recent years, with the establishment of the “four-hit” pathogenesis model and advances in gut mucosal immunity research, treatment strategies for IgAN have been shifting from traditional non-specific immunosuppression toward targeted and stratified therapies. In traditional Chinese medicine (TCM), diverse syndrome differentiation systems based on wind pathogen, kidney deficiency and blood stasis, damp-heat, and triple energizer theories have been developed, demonstrating unique value in symptom improvement, proteinuria reduction, and delaying renal function decline. In Western medicine, the 2025 Kidney Disease: Improving Global Outcomes (KDIGO) Clinical Practice Guideline for the Management of IgAN—the first standalone guideline for this condition—proposes a paradigm shift toward “simultaneous initiation” of etiological intervention and complication management. Renin-angiotensin system (RAS) blockers and sodium-glucose cotransporter-2 (SGLT2) inhibitors are now recommended as first-line supportive therapies, while novel agents including complement inhibitors (iptacopan), dual endothelin angiotensin receptor antagonists (sparsentan, atrasentan), targeted-release budesonide (Nefecon), and BAFF/APRIL-targeted therapies (telitacicept, sibeprenlimab, etc.) continue to emerge, offering additional treatment options for IgAN. This article systematically reviews the latest advances in the epidemiology, pathogenesis, clinical classification, and integrated TCM-Western medicine treatment of IgAN, aiming to provide references for clinical practice and future research.